2015
DOI: 10.1016/j.mayocp.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Diagnosis, and Treatment of Neck Pain

Abstract: Neck pain is the fourth leading cause of disability, with an annual prevalence rate exceeding 30%. Most episodes of acute neck pain will resolve with or without treatment, but nearly 50% of individuals will continue to experience some degree of pain or frequent occurrences. History and physical examination can provide important clues as to whether the pain is neuropathic or mechanical and can also be used to identify "red flags" that may signify serious pathology, such as myelopathy, atlantoaxial subluxation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
338
2
59

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(402 citation statements)
references
References 118 publications
3
338
2
59
Order By: Relevance
“…The differential diagnosis of neck pain may be considered based on the location and onset of pain and whether symptoms correlate with the clinically suspected mechanism of disease. 5,6 Common causes of neck pain involve neurogenic, mechanical, and secondary mechanisms, such as referred pain from a visceral or glandular structure. 5 This case report describes the acute onset of unilateral neck pain in an 88-year-old female without prior episode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential diagnosis of neck pain may be considered based on the location and onset of pain and whether symptoms correlate with the clinically suspected mechanism of disease. 5,6 Common causes of neck pain involve neurogenic, mechanical, and secondary mechanisms, such as referred pain from a visceral or glandular structure. 5 This case report describes the acute onset of unilateral neck pain in an 88-year-old female without prior episode.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Common causes of neck pain involve neurogenic, mechanical, and secondary mechanisms, such as referred pain from a visceral or glandular structure. 5 This case report describes the acute onset of unilateral neck pain in an 88-year-old female without prior episode. History and physical examination failed to raise clinical suspicion for common causes of acute neck pain, including those causes mediated by mechanical and neurogenic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical pain is the fourth leading cause of disability in adults, after lower back pain, depression and arthralgia (2). Epidemiologic studies estimate an annual prevalence of 30 to 50% in general population (3), and a systematic review reports the average frequency of 37.2% (4).…”
Section: Introductionmentioning
confidence: 99%
“…According to a study published in 2015 by Cohen et al, neck pain has an annual prevalence rate exceeding 30% and is the fourth leading cause of disability in the United States [10]. Fejer et al reported an estimated mean lifetime prevalence of neck pain in the world population to be around 50%, and the 1-month prevalence to be around 25% [11].…”
Section: Introductionmentioning
confidence: 99%